Mining activities and social sustainability: Lessons from coal transport mobilization activities in Jambi Province - Citra Darminto; Riri Maria Fatriani; M. Yusuf; Tawakkal Baharuddin (Center for Science and Technology, IAIN Surakarta, 2024)
With significant coal resource potential, Jambi Province faces serious challenges in the mobilization of coal transportation, a crucial element in the energy industry supply chain. This research examines the complexity problems arising from coal mobilization activities in Jambi Province and their social and environmental impacts. The research employs a qualitative method, utilizing documentation from online news sources and official government documents, including regional regulations. Data analysis is conducted using Nvivo 12 Plus. The findings reveal mismatch between licensing and regulations, leading to severe traffic disruptions. The sustainability of mining activities is faces significant challenges that require holistic solutions. Strategic policy recommendations include thorough audits of industry regulations, strengthening law enforcement, and promoting economic diversification. Other solutions involve more efficient traffic management, such as constructing dedicated lanes to alleviate pressure on general traffic. This research also highlights the importance of open and inclusive dialogue among all relevant stakeholders, with the government playing a key mediating role. Achieving balanced economic, social, and environmental sustainability in Jambi Province requires cross-sector collaboration and the active participation from all stakeholders.